Social Accounting Matrix for Okara District, Pakistan: A Water Resources Accountability in Pakistan (WRAP) Project Analysis - Davies, Stephen; Ali, Muhammad Tahir; Akram, Iqra; Hafeez, Mohsin (International Food Policy Research Institute, 2025)
The aim of this paper is to develop a document to guide the methodology and data resources used to develop a local Social Accounting Matrix (SAM) for Okara district in Punjab, Pakistan, and to provide an overview of the SAM results. Regional SAMs at lower administrative levels can be used to understand the regional economic impact of geographically targeted policies and shocks. The common data standards, procedures, and classification systems for national SAMs are adapted and modified for these regional SAMs. This approach and paper closely follow the development of SAM construction outlined in IFPRI’s NEXUS Project, which emphasized the need for greater transparency and consistency in SAM construction to strengthen model-based research and policy analysis in developing countries. Utilizing much of that Project’s general structure, our results permit comparisons at regional administrative scales, especially in agriculture and food systems including water resources dimensions. Additionally, this paper develops a companion method to evaluate direct and indirect water use associated with the economic changes produced from SAM analyses. We hope this methodology can be used to develop SAMs for other districts in the future.